2017
DOI: 10.1007/s12011-017-0955-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Selenium Supplementation on the Genotoxicity, Tissue Injury and Survival of Mice Exposed to Acute Whole-Body Irradiation

Abstract: The aim of the present study is to evaluate the radioprotective effect of low-dose selenium supplementation (multiple administrations) on radiation toxicities and mortality induced by lethal dose of whole-body irradiation (WBI). For this, BALB/c mice received sodium selenite (4 μg/kg body wt) intraperitoneally for five consecutive days and subjected to WBI at an absorbed dose of 8 Gy (Co, 1 Gy/min). Administration of sodium selenite was continued even during the post irradiation days three times a week till th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…By lowering the amount of lipid peroxide and increasing glutathione and glutathione peroxidase activity, sodium selenite significantly improved the oxidative stress response of the uterus and ovaries induced by radiation [11]. During whole-body irradiation treatment with sodium selenite, mice were protected against radiation-induced genotoxicity and DNA damage in peripheral leukocytes, but it did not keep the animals from mortality or gastrointestinal and hematopoietic lesions [12]. However, overall, in the further literature, the effects of sodium selenite described on the cellular radiation sensitivity are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…By lowering the amount of lipid peroxide and increasing glutathione and glutathione peroxidase activity, sodium selenite significantly improved the oxidative stress response of the uterus and ovaries induced by radiation [11]. During whole-body irradiation treatment with sodium selenite, mice were protected against radiation-induced genotoxicity and DNA damage in peripheral leukocytes, but it did not keep the animals from mortality or gastrointestinal and hematopoietic lesions [12]. However, overall, in the further literature, the effects of sodium selenite described on the cellular radiation sensitivity are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, survival following 10 Gy exposure was significantly dropped after selenomethionine treatment only [90]. Nevertheless, it is still an open question whether the results may indicate an advantage against the mortality sustained during nuclear emergencies [91].…”
Section: Oligoelementsmentioning
confidence: 94%
“…Glutathione peroxidase (GPX) has seven isoforms, i.e., GPX1‐7. [ 39 ] Superoxide dismutase (SOD) is an isoform of antioxidant enzymes, and SOD1 which plays an important role in treating and preventing free radical‐induced multiple diseases accounts for 85%. [ 40 ] Many studies have shown that Se‐enriched probiotics upregulate the mRNA expressions of GPX1, GPX4, and SOD1.…”
Section: Functional Improvement and Application Of Se‐enriched Probio...mentioning
confidence: 99%